Analysis of Learning Styles in Vocational Education in Grade 12 Students at SMK Negeri in Surakarta - Bagus Hirnov Baihaqi; Dwi Maryono; Dwi Esti Wardani (Pendidikan Teknik Informatika dan Komputer, Universitas Sebelas Maret, 2024)
Vocational education, especially in Vocational High Schools (SMK), plays a crucial role in preparing students for the world of work. Understanding student learning styles is an important aspect in the context of learning, because it affects the effectiveness of the learning process. Learning styles reflect students' preferences in receiving and processing information, becoming the foundation for developing more effective learning strategies. Each individual has unique ways of learning, such as visual, auditorial, and kinesthetic, which affect the understanding and retention of information. This study aims to analyze the learning styles of vocational students in the context of vocational education using qualitative research methods. The formulation of this research problem is how the characteristics of the learning style of vocational students in the vocational learning process. A qualitative approach is used to gain a deep understanding of students' preferences and tendencies in receiving and processing information. The data collection method involves interviews and observation to explore students' learning styles holistically. The results of this study are expected to provide insight into learning strategies that are more responsive and inclusive in accordance with the learning styles of vocational students, so as to increase their motivation, participation, and academic achievement in the vocational education environment.Keywords: Learning style, Learning style of vocational students, Vocational education